Elaboración de prótesis dentales en pacientes de mediana edad mediante la aplicación de impresiones 3d, revisión sistemática - Chirán Latacumba, Wilson Fernando (2025)
Introduction: Traditional dental prosthesis manufacturing has been a labor-intensive and occasionally imprecise process, requiring multiple visits and adjustments to ensure a proper fit. However, advancements in technology, particularly in the field of 3D printing, have opened up new possibilities in dentistry. Objective: To analyze the advantages and limitations of using 3D printing in the production of dental prostheses from 2019 to 2024, compared to traditional methods. Method: A qualitative systematic review using information sources such as PubMed and Google Scholar. Specific criteria were employed to include and exclude studies, prioritizing those in English or Spanish, available in open access, and focusing specifically on the application of 3D printing in the manufacture of dental prostheses and in dentistry. Results: The findings of the systematic review reveal a progressive increase in the publication of studies on 3D dental prostheses, with a significant rise in 2023. The advantages of this technology, including precision and customization, are highlighted, although challenges such as initial costs and material availability persist. In clinical practice, positive trends in precision and customization are observed, though challenges related to durability and biocompatibility remain. Conclusions: The use of 3D-printed dental prostheses offers clear benefits. However, to maximize clinical efficacy, it is essential to address the identified limitations and continue improving both the technology and professional training in its application.